Analisis Sentimen Tiktok: Wajib Militer dengan Metode Lexicon Based dan Naive Bayes Classifier - Saprizal, Arpan Mualief; Nor Anisa (Universitas Methodist Indonesia, 2024)
The issue of conscription in Indonesia has sparked a heated debate among the public, especially on the social media platform TikTok. This study aims to analyze public sentiment on the issue through analysis of TikTok user comments. The method used is lexicon-based sentiment analysis. Data of 5,212 comments were collected using web scraping techniques with the keyword